Sage, Saint and Sophist : Holy Men and Their Associates in the Early Roman Empire. - Anderson, Graham (Taylor and Francis, 2014)
Holy men, both pagan and Christian are persistent and puzzling figures in the religious life of the Roman Empire. In this first historical study of Holy Men for more than half a century, Dr Anderson applies techniques of literary analysis to throw light on the lifestyles and behaviour of these figures, from Jesus Christ to Peregrinus Proteus to dio Chrysostom, stressing their individuality as much as their common features. Sage, Saint and Sophist examines the variety of services, real or imaginary, that these colouful figures had to offer and how they maintained their credibility t.